The Pedagogy of Competencies in a Business Administration Undergraduate Course: the challenge presented by the transition from a pedagogical project to the teaching practice - Nunes, Simone Costa; Patrus-Pena, Roberto (Review of Business Management, 2011)
The aim of this paper is to analyse the discourse and the practice of the Pedagogy of Competencies in a Business Administration course from a private Higher-Education School in the state of Minas Gerais, Brazil, in order to identify and indicate the possibilities and challenges demanded by the implementation process taking place when moving from the course pedagogical project to a pedagogical practice. The focus of professional competencies distinguishes four dimensions, which were used as categories of analysis in this paper: identification, normalization, formation and certification/assessment. The project research methodology was qualitative-descriptive, carried out in three different occasions during three years. Data collection was done from the documentation of the course investigated as well as from semi-structured interviews. The research results indicate that, on one hand, there was a discourse to form students’ competencies. On the other hand, it was evident that there were some limitations related to such models of students’ formation. The conclusion reached has showed that even with indications of some elements of a Pedagogy of Competencies in the course investigated, they did not represent a systematic and articulate guidance given in a global way amongst other elements forming the teaching-learning process proposed by a students’ competency-based formation. Finally, we emphasize that this article is justified for its contribution to enhancing the knowledge on the implementation of this model of formation, and therefore to provide a basis for changes in the teaching-learning process as well as to enable actions aiming to overcome the challenges encountered in Business Management courses in relation to students’ competency-based formation. Key words: Teaching in Business Administration courses. Competency approach. Teaching-learning process.